Students’ Satisfaction Towards Online Learning Systems: Assessing Its Internal and External Factors - Tan, Sharon; Chuah, Francis; Hiram, Ting (Springer, Singapore, 2017)
This paper examines the internal factors (Internet self-efficacy and self-motivation) as well as an external factor (interaction) which affect university students’ level of satisfaction towards online learning systems. Field data were collected from 282 students from a public university. Data were analysed using multiple regression analysis. The outcome of the analysis suggests that these factors are significant predictors to students’ level of satisfaction when using a university’s online learning system.